Micropillar‐based culture platform induces epithelial–mesenchymal transition in the alveolar epithelial cell line. Issue 12 (27th August 2018) - Xu, Xiaoli; Ma, Lunkun; Wu, Yanjiao; Tang, Liling
Abstract: Topography and rigidity are two typical biophysical cues in extracellular matrix mechanical microenvironment. Extracellular matrix can regulate cells biological behaviors, including epithelial‐to‐mesenchymal transition (EMT). A growing body of evidence suggests that EMT plays an important role in the development of tumor and fibrosis. Moreover, EMT also contributes to drug resistance in cancer cells. Currently, the majority of studies about EMT are based on the induction of growth factors or cytokines in vitro. Here, we adopt polydimethylsiloxane (PDMS)‐micropillars‐based matrix platform to culture human alveolar epithelial cells for studying the influence of topography and rigidity on EMT. This study reports a previously undefined role of mechanical microenvironment in EMT induction. Different topography and rigidity can induce EMT directly without the use of exogenous cytokines. Notably, rigidity‐induced EMT activation is associated with the topography. Furthermore, we investigate preliminarily the role of PI3K/Akt signaling pathway in mechanical microenvironment regulation of EMT. These findings provide a fresh perspective to the researches of tumor and pulmonary fibrosis, and the potential platform for cell‐based drug screening. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 3165–3174, 2018.